Educational Technology and the Future of Teaching: Preparing for the Challenges and Opportunities Ahead - Jaradat, Hanan Ahmad Mohammad (International Journal on Integrated Education, 2023)
Education technology (EdTech) is becoming increasingly popular in classrooms and educational institutions worldwide. As technology advances, so does the need for educators to adapt to new teaching methods and tools. The integration of EdTech can offer many benefits, such as personalized learning, increased student engagement, and improved access to educational resources. However, its implementation also presents challenges, including the need for adequate training and support, concerns about equity, and potential distractions in the classroom. This paper explores the challenges and opportunities associated with integrating EdTech into education, particularly in higher education settings. It reviews the existing literature on this topic and provides recommendations for educators and institutions to effectively prepare for the future of teaching with EdTech. Overall, this paper aims to raise awareness of the potential of EdTech while also acknowledging the importance of careful consideration and preparation for its integration.